Bibliometric Analysis on the Topic of Trauma and Forgiveness: Trends and Future Research Directions (2016–2025) - Eka Prasetyawati; Fuad Nashori (Happiness: Journal of Psychology and Islamic Science, 2026)
Trauma is a complex psychological condition arising from overwhelming events such as violence, disaster, or profound loss, often leaving long-term effects on mental health and daily functioning. Recovery requires multidimensional approaches, and forgiveness has increasingly been recognized as a crucial therapeutic process. Rather than excusing harmful actions, forgiveness involves releasing resentment, which can reduce symptoms of PTSD, depression, and anxiety, while also enhancing physical health and relationships. Within Islamic psychology, forgiveness is emphasized as a spiritual pathway to restoring harmony with oneself, others, and God. Recent studies in Indonesia and globally highlight the effectiveness of forgiveness interventions across diverse populations, including survivors of violence and families of patients with chronic illness. To capture the evolving landscape of this research, the present study applies bibliometric analysis to 247 publications on trauma and forgiveness from 2016–2025. Using Biblioshiny and VOSviewer, it maps publication trends, collaboration networks, and thematic developments, providing a comprehensive overview and identifying future directions for integrative, culturally grounded trauma interventions.